Sistem Monitoring Daring pada Pengolahan Limbah Industri Kertas dan Pulp - Arif Sasongko; Marcellino Agung Christyo; alexander Marcelino Krismono; Aditya Rizky Maulana; elvayandri Muchtar; Andri Taufick Rizaluddin (Komputika : Jurnal Sistem Komputer, 2022)
As one of the largest wastewater producers in the world, the pulp and paper industry need to monitor the waste that they generated. To carry out this monitoring process, the majority of the pulp and paper industry still uses conventional offline methods to measure parameters in their wastewater treatment plants. The monitoring procedure is carried out by taking samples from the factory wastewater treatment plant and testing these samples in the laboratory. This procedure is very prone to errors caused by human. This method also cannot detect any violation, problem, or disturbance of the wastewater parameters in real time. In addition, in 2018, the Indonesian Ministry of Environment and Forestry issued a regulation requiring the pulp and paper industry to use a real-time online monitoring system for its wastewater treatment plant. This paper presents an implementation of the system. There are several parameters that must be measured, two of them are pH and TSS (Total Suspended Solids). To measure these parameters, the regulation states that the online measurement system is carried out using the relevant electric probe sensor. Then the measurement results are displayed online on a specified platform hence that users can observe the results. This implementation uses a pH sensor to measure pH and a conductivity sensor to measure TSS. A conductivity sensor is used as a substitute due to the high cost of TSS sensor. This article analyses also the accuracy of the measurement.